2018
DOI: 10.1038/s41467-017-02533-w
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal lysosomal dysfunction releases exosomes harboring APP C-terminal fragments and unique lipid signatures

Abstract: Defects in endolysosomal and autophagic functions are increasingly viewed as key pathological features of neurodegenerative disorders. A master regulator of these functions is phosphatidylinositol-3-phosphate (PI3P), a phospholipid synthesized primarily by class III PI 3-kinase Vps34. Here we report that disruption of neuronal Vps34 function in vitro and in vivo impairs autophagy, lysosomal degradation as well as lipid metabolism, causing endolysosomal membrane damage. PI3P deficiency also promotes secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 73 publications
(121 reference statements)
8
175
0
Order By: Relevance
“…Various studies have shown a causal relationship between lysosomal dysfunction and exosome secretion . Another study reported that increased secretion of atypical exosomes is a homeostatic response to counter lysosomal dysfunction to eliminate lysosomal waste . Our results confirm that lysosomal dysfunction results in significantly higher exosome release in ALD, suggesting a crosstalk between lysosomal dysfunction and the exosomal pathway.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Various studies have shown a causal relationship between lysosomal dysfunction and exosome secretion . Another study reported that increased secretion of atypical exosomes is a homeostatic response to counter lysosomal dysfunction to eliminate lysosomal waste . Our results confirm that lysosomal dysfunction results in significantly higher exosome release in ALD, suggesting a crosstalk between lysosomal dysfunction and the exosomal pathway.…”
Section: Discussionsupporting
confidence: 85%
“…(36,37) Another study reported that increased secretion of atypical exosomes is a homeostatic response to counter lysosomal dysfunction to eliminate lysosomal waste. (38) Our results confirm that lysosomal dysfunction results in significantly higher exosome release in ALD, suggesting a crosstalk between lysosomal dysfunction and the exosomal pathway. We found impaired autophagy and increased exosome production in the mouse model of ALD and also in patients with ALD.…”
Section: Discussionsupporting
confidence: 79%
“…The cytosolic side of the lysosomal membrane also serves as a signaling platform where mTORC1 interacts with cofactors in response to stress and initiates downstream cell responses . Recently, it has been proposed that lysosomal stress can induce the release of extracellular vesicles, such as exosomes, as an alternative pathway mediating the elimination of cellular waste …”
Section: Lysosomesmentioning
confidence: 99%
“…Impaired degradation and misfolded protein accumulation in long lived post‐mitotic cells such as neurons could lead to the secretion and propagation of pathogenic proteins . Exosomes might be used as vectors to evacuate these components out of the cells . Alzheimer's disease (AD) is a neurological disorder characterized by extracellular deposits of amyloid‐β peptide (Aβ).…”
Section: Exosomes and Homeostasismentioning
confidence: 99%
“…135 Exosomes might be used as vectors to evacuate these components out of the cells. 136 Alzheimer's disease (AD) is a neurological disorder characterized by extracellular deposits of amyloid-β peptide (Aβ). Aβ is derived from the processing of amyloid precursor protein (APP) by βand γ-secretases in the endosomal compartment.…”
Section: Neurological Peptides and Proteins Associated With Exosomesmentioning
confidence: 99%